Antibiotic resistance genes circulating in Nigeria: a systematic review and meta-analysis from the One Health perspective - Emmanuel N. Ugbo; Fleischer C. N. Kotey; Eric S. Donkor (BMC Medical Genomics)
Abstract Background The misuse of antibiotics in developing countries has created serious threats to public healthcare systems and reduced treatment options. Multidrug-resistant bacteria harbour antibiotic resistance genes that help them subdue the effectiveness of several available antibiotics. This review aimed to assess antimicrobial resistance genes circulating in Nigeria via a systematic review and meta-analysis. Methods A comprehensive literature search was performed using five electronic databases: PubMed, Web of Science, Scopus, Google Search, and African Journals Online (AJOL). Articles related to antibiotic resistance genes in Nigeria, published between January 1, 2015 and October 31, 2024, were included. The Newcastle-Ottawa scale (NOS) was used to assess the risk of bias. The meta-analysis for random effects was performed to determine the proportions and pooled prevalence of the resistance genes from the various One Health domains, as well as heterogeneity in the data, using R software (Version 4.3.3) and the metaprop package. Results Of the 762 articles retrieved, 56 (humans [n = 33], animals [n = 8], environment [n = 12], human/animal [n = 1], and human/animal/environment [n = 2]) from the six geopolitical zones in Nigeria met the inclusion criteria. The extended-spectrum beta-lactamase (ESBL) gene with the highest pooled prevalence was blaSHV (24.0% [95% CI: 12.0–44.0]), followed by blaCTX-M (23.0% [95% CI: 14.0–37.0]), and the least was blaTEM (18.0% [95% CI: 8.0–37.0]). Among the carbapenemase genes, blaKPC (33.0% [95% CI: 7.0–76.0]) was the most prevalent, followed by blaNDM (21.0% [95% CI: 9.0–41.0]), blaOXA (11.0% [95% CI: 2.0–46.0]) and the least was blaVIM (9.0% [95% CI: 3.0–26.0]). The mecA gene also had a high pooled prevalence (51.0% [95% CI: 14.0–86.0]). The pooled prevalence of the erm, sul, tet, and qnr genes ranged from 19.0% (95% CI: 8.0–38.0) to 27.0% (95% CI: 13.0–47.0). Some antibiotic resistance genes were shared among the three domains. Conclusion This systematic review and meta-analysis has demonstrated the co-existence of antibiotic resistance genes among bacteria causing infection in Nigeria, via the One Health approach. There is a need for future research on the circulation of antibiotic resistance genes in developing countries using internationally approved approaches to track down this menace.